The Strategy of the Qur'an Zone in Improving Students' Recitation Ability at the University Based on Pesantren - Azmi Zarkasyi; Jaziela Huwaida; Nada Mudrikah al Khudary; Umrodi Umrodi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research explores the effort of Markaz Qur’an in planning, implementing, and evaluating the tahsin recitation of the Qur’an using the Wafa method for Qur’an zone students at UNIDA Gontor. This research employs a qualitative case study approach. The data was collected through interviews, observation, and documentation. We analyzed using Miles and Huberman’s three-step method. The result is the planning of markaz quran for Qur’an zone student activities, which involves determining the setting of objectives, developing strategies, and utilizing teaching resources to achieve the goal. The implementation consists of Reading Practice, Application of Tajwid, pronunciation practice, supervision, and correction.